Keratoconjunctivitis as a Single Entity in X-linked Agammaglobulinemia?. (16th March 2023) - Mielke, Stefan; Grundel, Bastian; Schmidt, Sebastian M.; Tost, Frank
ABSTRACT: Purpose: To report a case of a male patient with a severe corneal and conjunctival immunopathy likely caused by an X-linked agammaglobulinemia. Methods: A clinical case report with observation results from 2001-2021. Results: A severe corneal immunopathy of both eyes is reported in a retrospective long-term observation of nearly twenty years in a 32-year-old male patient with X-linked agammaglobulinemia (XLA). A chronic progressive corneal scarring with a loss of visual acuity and typical symptoms of a phlyctenular keratoconjunctivitis were observed. Conclusion: Whereas steroid eye drops like dexamethasone could control the symptoms and the corneal scarring progression as short time therapy options, ciclosporin A eye drops showed problems in therapy adherence in long-time use. Antibiotic eye drops supported the anti-inflammatory therapy effects, but no typical pathogen was detected. Antineovascular subconjunctival application did not show any relevant effect in one-time use. Artificial tears were needed as basic therapy.